151k views
1 vote
Rewrite the expression x^3+10x^2+13x+39/x^2+2x+1 in the form of q(x)+r(x)/b(x)

User Broti
by
4.7k points

1 Answer

7 votes


(x^3+10x^2+13x+39)/(x^2+2x+1)


x^3=x\cdot x^2, and
x(x^2+2x+1)=x^3+2x^2+x. Subtracting this from the numerator gives a remainder of


(x^3+10x^2+13x+39)-(x^3+2x^2+x)=8x^2+12x+39


8x^2=8\cdot x^2, and
8(x^2+2x+1)=8x^2+16x+8. Subtracting this from the previous remainder gives a new remainder of


(8x^2+12x+39)-(8x^2+16x+8)=-4x+31


-84x is not a multiple of
x^2, so we're done. Then


(x^3+10x^2+13x+39)/(x^2+2x+1)=x+8+(-4x+31)/(x^2+2x+1)

User Skybobbi
by
4.8k points